Numerical Simulation of Fluid Flow Around Circular Cylinder and Three Passive Controls to Reduce Drag Coefficient at Re=500 - Chairul Imron; Amirul Hakam; Basuki Widodo; Tri Yogi Yuwono ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2020)
Numerical experiments and simulations of fluid flow through the outer surface of a circular cylinder and three passive controls have been investigated to determine the proper configuration of three passive controls in reducing the drag coefficient. One of passive controls is placed in front of the cylinder with distance ratio (S:D) = 2:4 and the other two passive controls are placed behind the cylinder with distance ratio (T:D) = 1:6;1:8. The angle between two passive controls behind the cylinder are a =30 deg;60 deg;90 deg;120 deg. The Navier-Stokes equations for incompressible, viscous and unsteady fluid flows is solved based on SIMPLE (Semi-Implicit for Pressure-Linked Equations) algorithms and discretized using finite-difference method. The difference in a affects the reduction in the drag coefficient significantly. The best configuration of three passive controls design is one of passive controls put at the distance ratio S=D = 2:4;T=D = 1:6 and a = 60. This configuration can reduce the drag coefficient optimally to 21.2109%.